Strategy for South African public libraries to bridge the digital divide - Mphidi, Hamilton Hamilton (University of Pretoria, 2017)
This thesis reports on a study that investigated the role of public libraries in addressing the digital divide in South Africa. The study started in 2006. This study addressed the main research question: "How should a theoretical model look for South African public libraries to contribute to bridging the digital divide?" The central research problem was further addressed by asking the following questions: • What are the scope and implications of the digital divide? (These include the meaning of the concept, the dimensions and the factors leading to the digital divide.) • What has been reported on the role of libraries (including information services) in bridging the digital divide? • What have libraries in South Africa done to address the digital divide, and which possibilities are foreseen? • How can South African libraries be positioned to contribute to bridging the digital divide? The study followed a survey method using interviews with directors of Provincial Library Services (or their representatives), which are the controlling bodies of public libraries in South Africa, questionnaires distributed to representative staff members of participating public libraries in Gauteng, Limpopo and KwaZulu-Natal and individual interviews with selected heads/representatives of public libraries in Gauteng, Limpopo and KwaZulu-Natal. Data collected through the questionnaires were both quantitative and qualitative. Data was collected between 2011 and 2012. Quantitative data were analysed using Statistical Package for Social Sciences (SPSS), while qualitative data from interviews were analysed by content analysis and thematic categorising of information. In October 2015 a follow-up study of limited scope was conducted with three representatives from the three provincial library services to establish developments since the first round of data collections. Seven out of nine directors of Provincial Library Services in South Africa participated in the study. Furthermore, 247 public libraries from Gauteng, Limpopo and KwaZulu-Natal out of 463 public libraries and 18 heads/representatives of public libraries participated in this study. Findings on the opinions expressed on the role of public libraries in bridging the digital divide include the following: providing access to information and communication technologies (ICTs), offering information literacy and ICT literacy training, providing information to reduce the gap between "haves" and "have-nots", providing communities with equal, free access, reaching out and spreading ICTs to those who may not have online access and support and facilitating and promoting information exchange and communication between citizens and the government. The overall findings from the study were that although provincial library services have documents containing information on their mission and vision, their mission and vision statements do not address the digital divide or shed any light in this regard. The study found that provincial library services aimed to support public libraries to provide information resources, services to communities and access to information through ICT via targeted fund transfers to municipalities. None of the provincial library services included in the study had an explicit policy and strategies aligned to its vision and mission to guide and enable it in addressing the digital divide. Although all provincial library services included in the study had access to computer facilities in their headquarters, there were still disparities in the number of computer facilities available. It was also found that none of the provincial library services had its own website at the time of the study. They depended on the websites of their parent organisations. The study found that very few provincial library services had information technology (IT) units/departments charged with the responsibility of taking care of ICT facilities. They depended on external ICT service providers or the IT departments of their parent organisations to maintain the library's ICT infrastructure.
EdTechHub.ItemAlsoKnownAs: 2129771:7QDKMKX7